Resistance and Truth-Telling: Antigone in Twentieth Century´s Literature - Delaini, Lucia (2015)
Throughout the Western literary tradition, Antigone maintains a place of honour in the narration of power struggles. In recent times, her strenuous opposition to Creon’s absolute power inevitably recalls the role of resistance within the twentieth century’s totalitarian context. However, the heroin’s juxtaposition to Creon undergoes a significant change in contemporary, literary versions of typical Antigonean acts. In particular, Orwell’s Nineteen Eighty-Four and Wolf’s Cassandra show a situation similar to the polarized setting on Sophocles’ scene, but with a very different formulation of the dynamics between the parts. In the light of Michel Foucault’s analysis of power structures, this new relationship can be read as an attempt, on the resistant’s part, at re-subjectification. One of the fundamental practices of this process is that of truth-telling, analyzed by the late Foucault in its classical formulation of parrhesia. By applying the philosopher’s breakdown of this concept to the endeavour performed by the novels’ protagonists, the political value of parrhesia emerges as both a form of resistance and a requirement for any anti-totalitarian settings. However, the pervasiveness of power binds truth-telling with a necessary process of “care of the self” leading to selfknowledge: a process that only seems to be available for elite groups. In the aftermath of last century’s totalitarianism, these Antigones descend to their death in order to deliver a powerful message of resistance, which is deeply personal and political, external and internal. Their main question to us remains, what kind of Antigones do we want for our society?